Evolution of information-driven HIV/AIDS policies in China. - Sun, Xinhua; Lu, Fan; Wu, Zunyou; Poundstone, Katharine; Zeng, Gang; Xu, Peng; Zhang, Dapeng; Liu, Kangmai; Liau, Adrian (International journal of epidemiology, 2010)
As China continues to commit to universal access to HIV/AIDS prevention, treatment and care services, its HIV/AIDS policies have become increasingly information driven. We review China's key national-level HIV/AIDS policies and discuss policy gaps and challenges ahead.
Keywords: Acquired Immunodeficiency Syndrome; Anti-Retroviral Agents; Blood Donors; China; Condoms; Counseling; Health Policy; Health Services Accessibility; HIV Infections; Humans; Mass Screening; Methadone; Needle-Exchange Programs; Prejudice; Prostitution; Substance Abuse, Intravenous; Travel